On the source of risk aversion in Indonesia using micro data 2007 - Muhammad Ryan Sanjaya (Kiel Institute for the World Economy (IfW), 2013)
Many conventional economic analyses assume that risk preference is taken as given and do not give much scrutiny on it. However, empirical studies show that risk preference is not random: shocks and predetermined characteristics can determine risk preference. This study tried to see if these potential determinants together affect risk aversion in Indonesia using 2007 micro data. The author found that there is limited evidence that shocks and predetermined characteristics can affect risk preference. There is a preliminary indication that risk preference was not only driven by the individual's wealth and demographic factors (that can be easily controlled), but also by the individual's time preference.
Keywords: O12; D81; 330; risk aversion; preference; Indonesia; microeconometrics